DIFUSI INOVASI TEKNOLOGI PENGELOLAAN SAMPAH PADA MASYARAKAT - Sidik, Muhammad Ansorudin (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2007)
The diffusion of Waste Management System to the society should be followed by the change of not only their knowledge and attitude, but also their behavior. To find out the effects of the diffusion to the society, some measurements can be used. These are the number of society adopted the system and how fast the society can adopt it. In order to measure the success of its implementation, the knowledge on the natures of innovation in waste management technology is required, as well as the components influencing how fast it is adopted. By doing so, the system socialization is expected to be more acceptable by all parties. It is needed to avoid the incompleteness of waste management system socialization carried out so far by society and government elements.